The Relationship between Family Affective Functioning and Bullying Behavior in School-Age Children - Roemahlaiselan, Sindy Olivia; Windarwati, Dwi Heni; Hidayah, Ridhoyanti; Nova, Renny (Promotion and Prevention in Mental Health Journal, 2023)
Bullying is a global phenomenon. One of the factors of bullying is family affective function. This study analyzes the relationship between family affective function and bullying behavior in school-age children at SDK Sang Timur Malang. This study used a cross-sectional approach. The measurement tools used were the bullying behavior questionnaire (Sejiwa) and the family affective function questionnaire (Family Assessment Device / FAD). The number of samples in this study was 44 students. Characteristics of respondents aged 10-12 years. The family affective function is in the moderate category, and most of the components respect each other. Bullying behavior is in the low category and most of the verbal bullying. Bivariate analysis shows a relationship between family affective function and bullying behavior in school-age children at SDK Sang Timur Malang (Spearman Rank test, p=0.002). The suggestion for this research is that it can be used as a group counseling therapy for families. This therapy, which involves structured sessions led by a trained counselor, aims to provide the concept of good family affective function so that it can reduce the incidence of bullying behavior. This therapy can be applied when conducting school interventions when students practice mental nursing in the community by providing solutions regarding bullying behavior and in the family community by providing counseling on family affective functions to families.